2019
DOI: 10.26442/2075082x.2019.4.190649
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for falls in patients with arterial hypertension

Abstract: Falls are a serious multi-factorial problem faced by the elderly persons which is associated with serious complications, loss of functional autonomy, disability and death. One of the common comorbidities among the elderly persons is arterial hypertension (AH) which increases the risk of falls. Aim. To study the risk factors for falls among patients with AH. Materials and methods. Examined 155 patients of geriatric department with the presence of at least one fall in the last year: 133 (85.8%) women (75,29±8.31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This finding is consistent with the results of Van Rensburg [23]. Khovasova's study showed that arterial hypertension could increase the risk of patients falling [11]. Hypertension may be associated with impaired blood flow to patients' central nervous systems and affect their balance when getting out of bed and moving.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with the results of Van Rensburg [23]. Khovasova's study showed that arterial hypertension could increase the risk of patients falling [11]. Hypertension may be associated with impaired blood flow to patients' central nervous systems and affect their balance when getting out of bed and moving.…”
Section: Discussionsupporting
confidence: 90%
“…A study showed that 24.5% of patients undergoing CABG develop temporary delirium [8]. Moreover, the occurrence of cardiac arrhythmias after CABG may increase the risk of falling by impairing cerebral circulation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%